KAIDAH FIQH AL-UMURU BI MAQASIDIHA DALAM PENYELESAIAN SENGKETA HARTA BERSAMA DALAM PERKAWINAN MENURUT HUKUM ISLAM DI INDONESIA - A. Mansur; Dwi Dasa Suryantoro (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze the application of the Al-Umuru Bi Maqasidiha rule as a normative basis in the arrangement of joint property of a couple according to Islamic family law in Indonesia. This rule emphasizes that the application of the law must always pay attention to the purpose of sharia, namely justice, benefit, and protection of individual rights, so that it is not only formalistic but also substantive. The research uses a normative approach by analyzing classical and contemporary fiqh literature, the provisions of the Compilation of Islamic Law (KHI), and related laws and regulations. The analysis focused on the position and function of fiqh rules in assessing the appropriateness of property distribution, including formal and non-formal contributions, as well as the protection of the rights of women and vulnerable parties. The results of the study show that the rules of Al-Umuru Bi Maqasidiha function as a normative guideline that bridges classical law with the socio-economic dynamics of the modern family. This rule ensures that the arrangement of joint property is in harmony with maqasid al-shari'ah, provides direction for a fair, proportionate, and contextual interpretation of law, and reinforces the relevance of contemporary Islamic family law. This research confirms that the normative application of fiqh rules can be an important instrument in realizing substantive justice and benefits for all parties in the framework of Islamic family law in Indonesia.